Maximal cytoreduction is related to improved disease-free survival in low-grade ovarian serous carcinoma. Issue 3 (June 2019) - Kimyon Comert, Gunsu; Turkmen, Osman; Mesci, Cigdem Guler; Karalok, Alper; Sever, Ozge; Sinaci, Selcan; Boran, Nurettin; Basaran, Derman; Turan, Taner
Objective: To evaluate the factors predicting oncologic outcomes in low-grade ovarian serous carcinoma (LGOSC). Methods: Seventy patients with LGOSC were included in the study. According to the residual disease present at the end of the initial cytoreductive surgery (CRS), surgical outcomes are defined as follows: maximal CRS for absence of macroscopic residual tumors, optimal CRS for macroscopic residual tumors with diameters ranging from 0.1 to ⩽1 cm diameter, and suboptimal CRS for macroscopic residual tumors measuring >1 cm in diameter. Results: Five-year disease-free survival (DFS) and cancer-specific survival (CSS) were 61% and 83%, respectively. Surgical outcomes were suboptimal in 3 (4.3%) patients, optimal in 8 (11.4%) patients, and maximal in 59 (84.3%) patients. Stage and surgical outcomes were related to DFS ( p < 0.05). Compared with maximal CRS, the presence of residual tumors (suboptimal and optimal debulking) was related to threefold increased risk of disease failure (recurrence or progression) (hazard ratio [95% confidence interval] 3.00 [1.27–7.09]; P =0.012). CSS was associated with disease stage alone ( P =0.03). Advanced stage was related with lower DFS and CSS. Conclusions: Maximal CRS facilitates an improvement in DFS. Achieving no residual disease after the completion of surgery should be a cornerstone of LGOSC management.